EFFECTS OF FUT1 AND MUC4 POLYMORPHISMS ON SPERM QUALITY TRAITS OF LANDRACE AND YORKSHIRE PIGS UNDER TROPICAL CONDITIONS IN NORTHERN VIETNAM - D. D. Luc; H. X. Bo; N. H. Thinh; H. Q. Hanh; D. T. Phuong; T. X. Manh; N. V. Hung; V. D. Ton; F. Farnir (Journal of Animal and Plant Sciences, 2022)
This study was aimed to determine allelic and genotypic frequencies of two single nucleotide polymorphisms (SNPs) located in alpha (1) fucosyltransferase (FUT1) gene and mucin 4 (MUC4) gene, and effects of these SNPs on sperm quality traits of Landrace and Yorkshire pigs. A total of 4771 ejaculates from 63 Landrace and 34 Yorkshire boars have been collected from May 2015 to July 2018 at nucleus breeding pig farm in Vietnam. The sperm quality traits were ejaculate volume, spermatozoa motility, sperm concentration and total number of spermatozoa in ejaculate. Hardy-Weinberg equilibrium was assessed using Fisher exact test. A mixed model was used to test the effects of fixed and random factors on the sperm traits. The fixed factors were genotype, breed, age of boar, month of the year, while boar ID number was included in the model as a random effect, allowing to properly model repeated measurements. These resistant genotypes were absent in Landrace. While the frequency of resistant genotypes AA for FUT1 (0.03) and GG for MUC4 (0.16) was relatively low in Yorkshire boar population. The only detected significant effect of FUT1 and MUC4 on semen quality traits had a positive effect of the resistant genotype GG of MUC4 on sperm motility (P = 0.015). The two SNPs located in FUT1 and MUC4 did not affect sperm traits except sperm motility. Consequently, the selection based on theseresistant genotypes does not seem to negatively affect the monitored sperm traits.
Keywords: SNP; diarrhea resistant; semen; swine